COVID-19 vaccine immunogenicity in people with HIV. (1st January 2023) - Costiniuk, Cecilia T.; Singer, Joel; Lee, Terry; Langlois, Marc-André; Arnold, Corey; Galipeau, Yannick; Needham, Judy; Kulic, Iva; Jenabian, Mohammad-Ali; Burchell, Ann N.; Shamji, Hasina; Chambers, Catharine; et al.
Abstract : Objectives: Many vaccines require higher/additional doses or adjuvants to provide adequate protection for people with HIV (PWH). Our objective was to compare COVID-19 vaccine immunogenicity in PWH to HIV-negative individuals. Design: In a Canadian multi-center prospective, observational cohort of PWH receiving at least two COVID-19 vaccinations, we measured vaccine-induced immunity at 3 and 6 months post 2nd and 1-month post 3rd doses. Methods: The primary outcome was the percentage of PWH mounting vaccine-induced immunity [co-positivity for anti-IgG against SARS-CoV2 Spike(S) and receptor-binding domain proteins] 6 months post 2nd dose. Univariable and multivariable logistic regressions were used to compare COVID-19-specific immune responses between groups and within subgroups. Results: Data from 294 PWH and 267 controls were analyzed. Immunogenicity was achieved in over 90% at each time point in both groups. The proportions of participants achieving comparable anti-receptor-binding domain levels were similar between the group at each time point. Anti-S IgG levels were similar by group at month 3 post 2nd dose and 1-month post 3rd dose. A lower proportion of PWH vs. controls maintained vaccine-induced anti-S IgG immunity 6 months post 2nd dose [92% vs. 99%; odds ratio: 0.14 (95% confidence interval: 0.03, 0.80; P  = 0.027)]. In multivariable analyses, neither age, immune non-response, multimorbidity, sex, vaccine type, or timing between doses were associated with reduced IgG response. Conclusion: Vaccine-induced IgG was elicited in the vast majority of PWH and was overall similar between groups. A slightly lower proportion of PWH vs. controls maintained vaccine-induced anti-S IgG immunity 6 months post 2nd dose demonstrating the importance of timely boosting in this population.